Hidden histories : Palestine and the Eastern Mediterranean - Raʻad, Basem L. (Pluto Press, 2010)
"This is a courageous foray into one of the most fraught terrains of history. Those who seek to understand one of the world's most misunderstood regions should read closely Ra'ad's meticulous retracing of its overwrought human record.---Djelal Kadir, The Edwin Erle Sparks Professor of Comparative Literature, Pennsylvania State University" "Ra'ad's book is right on the mark. Scholars have created a politically tendentious history of Palestine, effectively marginalizing every alternative history and supporting an intensifying effort to displace modern Palestinians from their cultural roots. We can now "unlearn" much of what we have been given to know about this land.---Thomas L. Thompson, Professor Emeritus, University of Copenhagen" "Ra ad draws upon the latest research in archaeology, linguistics and history to expose how the past has been appropriated for orientalist and colonialist purposes. This is a brilliant tour-de-force of recovery, de-colonization, re-vision, and inclusivity.---Hilton Obenzinger, Standford University, author of American Palestine: Melville, Twain and the Holy Land Mania" "For thousands of years, the region of Palestine and the East Mediterranean has been denied an Indigenous voice for an inclusive history. Three religions ascribe their origins to this part of the world, appropriating and re-appropriating the "Holy Land" time and again. This book offers a powerful corrective to common understandings. It emphasizes Palestine's long history and dispels many old and new myths-covering issues of religious origins and sacred sites, identity and self-colonization, and the retrieval of ancient heritage"--Jacket